Relations among psychopathy, moral competence, and moral intuitions in student and community samples - Gay, Jeremy G. (Legal and criminological psychology, 2018)
Purpose. The nature of moral decision-making in those with pronounced psychopathic traits has been passionately debated, both in scientific literature and in the public policy arena. Research investigating the relationship between psychopathic traits and moral decision-making capacities has been largely inconclusive. However, recent research suggests individuals with elevated psychopathic traits may exhibit abnormal moral intuitions regarding the prevention of harm (Harm) and promotion of fairness (Fairness). Although moral intuitions are widely assumed to be related to moral judgement, no research has simultaneously examined the relations among psychopathy, moral intuition, and moral judgement. Methods. We hypothesized that psychopathic traits would not be directly related to moral judgement outcomes but would be indirectly related by way of Harm and Fairness moral intuitions. To test these hypotheses, 121 undergraduate students and 205 community residents, across two studies, completed measures of psychopathy, moral intuitions, and moral judgement. Results. Higher psychopathy scores were associated with decreased concerns about preventing harm and promoting justice across both samples. Individuals higher in psychopathic traits did not evidence deficits in moral judgement. Conclusions. Our findings indicate that, although individuals with elevated psychopathic traits may organize their sense of morality differently, they can accurately discern moral from immoral decisions.